Complete chloroplast genome of endangered Bruguiera hainesii C.G.Rogers 1919 and phylogenetic analysis with associated species - Viet Ha Tran; Thi Thu Trang Hoang; Mai Phuong Pham; Dinh Giap Vu; Quoc Khanh Nguyen; Dinh Duy Vu (Biomedical and Biotechnology Research Journal, 2023)
Background: Bruguiera hainesii C.G. Rogers 1919, a true mangrove tree is a critically endangered species (CR) in Vietnam. This species is restricted to the Con Dao National Park, Ba Ria-Vung Tau province, where it occurs in very tiny populations. However, the exploration of the chloroplast genome of B. hainesii in Vietnam has a serious lack of information. It is extremely challenging to promote the conservation of B. hainesii. Therefore, urgently required to discover and comprehend the chloroplast genome of B. hainesii. Methods: To detect evolutionary analysis between mangroves, we sequenced the complete chloroplast genome of B. hainesii using next-generation sequencing technology (Illumina Hiseq X Ten). Results: We sequenced and assembled the complete chloroplast genome of B. hainesii, which was deposited in GenBank as accession number OR086085. The DNA was circular with 164,305 bp length, comprising 37% GC. The genome contained a large single-copy region of 91,724 bp, inverted repeat regions of 26,360 bp, and a short single-copy region of 19,861 bp. Furthermore, it contained 130 genes, consisting of 83 protein-coding genes, 37 tRNAs, and 8 rRNAs. We detected 131 single-sequence repeats, including 119 mononucleotides, 11 dinucleotides, and one trinucleotide. Phylogenetic analysis showed strong support that B. hainesii was sister to B. cylindrica. Conclusions: The findings in this study provide a foundation for species identification, evolutionary genetics, and the conservation of endangered B. hainesii in Vietnam.